2018
DOI: 10.1001/jamapsychiatry.2017.4432
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Change in Fentanyl Prevalence in a Community-Based, High-Risk Sample

Abstract: Planning for the implications of nonprescribed fentanyl use relies on multisource forensic 1,2 or clinical samples. 3,4 Complementing these descriptions, we report a prospective longitudinal study of change in urine fentanyl prevalence in a highrisk, community-based sample. 5Methods | Directly assessed participants were from a health outcomes study of people living in an impoverished neighborhood of Vancouver, Canada. 5 For context, overall over-dose deaths (Vancouver) and first responder calls (Vancouver and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 6 publications
(19 reference statements)
1
34
1
Order By: Relevance
“…Unlike similar Canadian studies , we found no evidence of fentanyl‐laced heroin through urine screens among people who inject ‘heroin’ in Sydney, Australia. Regarding feasibility and acceptability, clients appeared interested in whether their heroin contained fentanyl, as demonstrated among similar populations elsewhere .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike similar Canadian studies , we found no evidence of fentanyl‐laced heroin through urine screens among people who inject ‘heroin’ in Sydney, Australia. Regarding feasibility and acceptability, clients appeared interested in whether their heroin contained fentanyl, as demonstrated among similar populations elsewhere .…”
Section: Discussioncontrasting
confidence: 99%
“…Urine screening for fentanyl and derivatives is a relatively easy way of incorporating surveillance within client services. Four Canadian studies have utilised urine screening in community settings to monitor the unintended consumption of fentanyl (and analogues). In 2015, Amlani et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in a recent study in Canada, 75% of individuals reporting nonmedical opioid use and denying fentanyl use had their urine test positive for fentanyl [43]. Another study showed that, among patients denying known exposure to fentanyl and seeking opioid withdrawal management, twothirds tested positive for fentanyl in urine [44].…”
Section: Discussionmentioning
confidence: 92%
“…On initial assessment, the patient self-reported injecting 200 mg of heroin daily 200 mg of crystal methamphetamine every 3 days. The actual amounts used was difficult to measure given the variability in chemical make-up and potency of heroin and other street drugs in Vancouver, including their adulteration with fentanyl and other contaminants [22,23].…”
Section: Case Presentationmentioning
confidence: 99%